2013
DOI: 10.1089/dia.2012.0242
|View full text |Cite
|
Sign up to set email alerts
|

What We Can Really Expect from Telemedicine in Intensive Diabetes Treatment: 10 Years Later

Abstract: During the last 10 years many new telematic systems aiming at support of diabetes treatment have been designed and developed. Most systems that were applied in clinical randomized trials used the classical approach, with data transfers from patients performed usually once every few days. In the few available meta-analyses of these trials, a significant improvement of the mean hemoglobin A1c was demonstrated in patients using telematic systems. However, the magnitude of this improvement in comparison with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
(44 reference statements)
0
2
0
2
Order By: Relevance
“…14,20,[25][26][27] Specialists in family medicine, primary care and internal medicine usually implement home telemonitoring of chronic diseases and blood pressure monitoring in their studies, and there are a few research groups focused on telediabetology. 28,29 Telepathology was introduced in the 1990s in Poznań with the description of remote automatic microscope functionality, and several more papers focused on additional telepathology applications. 23,24,[30][31][32] We observed a significant impact of research focusing on otorhinolaryngology ("ear, nose and throat" or ENT), especially with using telemedicine for cochlear implant fitting.…”
Section: Discussionmentioning
confidence: 99%
“…14,20,[25][26][27] Specialists in family medicine, primary care and internal medicine usually implement home telemonitoring of chronic diseases and blood pressure monitoring in their studies, and there are a few research groups focused on telediabetology. 28,29 Telepathology was introduced in the 1990s in Poznań with the description of remote automatic microscope functionality, and several more papers focused on additional telepathology applications. 23,24,[30][31][32] We observed a significant impact of research focusing on otorhinolaryngology ("ear, nose and throat" or ENT), especially with using telemedicine for cochlear implant fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reviews have shown that telemedicine has some success in treating patients with type 1 diabetes. 511 However, randomized controlled trials are not available to show the efficacy of using telemedicine to treat patients with diabetes who have a lifestyle comparable to a soldier. There are case reports of athletes with type 1 diabetes who have been monitored during endurance sports, 12–15 some with continuous glucose monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Separate Kosteneinsparungen durch die Digitalisierung in Form von telemedizinischen Innovationen zeigen sich in dieser Arbeit nicht. Sie werden jedoch in der Literatur mehrfach beschrieben [41,42].…”
Section: Diskussion Und Schlussfolgerungenunclassified